Adrenal myelolipoma with keratoconus: A novel clinical association - Dutta, Deep (Medknow Publications & Media Pvt Ltd, 2012)
Adrenal myelolipoma is a benign metaplastic collection of reticuloendothelial cells and adipose tissue, believed to be secondary to chronic stimulation of the adrenals. Keratoconus is the most common corneal ectasia of unknown pathogenesis. Altered expression of proteinases, proteinases inhibitors, and cytokines are believed to have a role. We report for the first time, the occurrence of adrenal myelolipoma in a 52-year-old man with bilateral keratoconus with right corneal scarring for 13 years, who had presented with abdominal pain and heaviness for 4 weeks. Computerized tomography abdomen revealed 7.4 × 7.0 × 6.6 cm hypo-dense variegated left adrenal mass [–71 to –51 Hounsfield Unit (HU)] with smooth borders and poor contrast uptake, suggestive of adrenal myelolipoma, which was biochemically non-functional in view of normal overnight dexamethasone suppressed cortisol (1.4 mcg/dl), 24 h urinary fractionated metanephrines [metanephrines 57 mcg/day (53-341); normetanephrines 95 mcg/day (88-444)], androgen levels [dehydroepiandrostenedione-sulphate 112 mcg/dl (21-123); testosterone 542 ng/dl (275-1200)] with normal visualization of the contralateral adrenal. The cause of this association could not be determined. However, it may be hypothesized that altered adrenal steroid metabolism may have some role in the development of myelolipoma in our patient with keratoconus; in view of increased occurrence of myelolipoma in patients with congenital adrenal hyperplasia (CAH), isolated report of keratoconus in twins with CAH and mice model of keratoconus demonstrating the role of androgens in the development of keratoconus.